Returns to Individual Traders of Futures: Aggregate Results - Hartzmark, Michael L. (Journal of Political Economy, 1987)
By means of a data set previously unavailable for academic research, actual trading histories of individual futures traders are examined. With this more detailed data, the author is able to (1) test the risk/return hypothesis directly; (2) include a much larger segment of the market than before; and (3) use actual instead of hypothetical t rading strategies. It is shown that the commercial (hedging) traders are most profitable, while noncommercial (speculative) traders earn n egative or zero profits. Because speculators are not receiving reward s for the risks they willingly absorb, the theory of normal backwarda tion and its extension can be rejected. Copyright 1987 by University of Chicago Press.